2015
DOI: 10.1111/jsm.12817
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Altered Sex Ratio in Clinic-Referred Adolescents with Gender Dysphoria

Abstract: Introduction The number of adolescents referred to specialized gender identity clinics for gender dysphoria appears to be increasing and there also appears to be a corresponding shift in the sex ratio, from one favoring natal males to one favoring natal females. Aim We conducted two quantitative studies to ascertain whether there has been a recent inversion of the sex ratio of adolescents referred for gender dysphoria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
236
2
26

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(283 citation statements)
references
References 26 publications
19
236
2
26
Order By: Relevance
“…To our knowledge, this has not been documented formally in the empirical literature and is distinctly different from the sex ratios of trans adolescents and trans adults, which point toward near parity. 18,19,44,45 Whether trans people who transition later in life constitute a different group compared to their younger counterparts has been vociferously debated. 46,47 Trans people who transition later in life may have different psychosocial characteristics, but the exact etiology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this has not been documented formally in the empirical literature and is distinctly different from the sex ratios of trans adolescents and trans adults, which point toward near parity. 18,19,44,45 Whether trans people who transition later in life constitute a different group compared to their younger counterparts has been vociferously debated. 46,47 Trans people who transition later in life may have different psychosocial characteristics, but the exact etiology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the number of referrals being received by gender identity clinic services in North America and Europe has increased substantially over the years [71,72]. The increase in prevalence over the years is likely to be due to several factors: the increased visibility of trans people in the media, which likely contributes to at least a partial de-stigmatisation of being trans [71]; the wide availability of information on the internet about trans people, which also likely contributes to de-stigmatisation [71]; the increased awareness of the availability of biomedical treatment [2,3,4]; and the development of societal tolerance towards trans individuals [73]. Perhaps trans individuals, with ASD, have less reservation to seek referral to gender identity clinic services, as explained above, and therefore constitute a relative overrepresentation within clinical samples.…”
Section: Limitations Of the Current Literaturementioning
confidence: 99%
“…Prevalence estimates are strongly affected by recruitment strategies, diagnostic criteria, treatment availability, and eligibility 23,24 . Moreover, an interesting study has indicated that the numbers of referrals to specialized clinics for gender dysphoria have increased between 2006 and 2013 together with a corresponding shift in the sex ratio, from one favouring natal males to one favouring natal females 26 . Although gender-variant behaviour has been shown to be frequent in children, ranging from 2-23% for natal males and 4-39% for natal females 27,28 , numbers are definitely smaller when considering gender-variant adolescents reporting discontent with their assigned gender and/or seeking hormone treatment or some form of surgery (0.6% of the natal males and 0.2% of the natal females) 29 .…”
mentioning
confidence: 99%